2008
DOI: 10.1167/iovs.07-1472
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin/Hephaestin Knockout Mice Model Morphologic and Molecular Features of AMD

Abstract: DKOs have age-dependent iron accumulation followed by retinal degeneration modeling some of the morphologic and molecular features of AMD. Therefore, these mice are a good platform on which to test therapeutic agents for AMD, such as antioxidants, iron chelators, and antiangiogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 44 publications
5
96
1
Order By: Relevance
“…Mice homozygous for a null mutation in the hemochromatosisassociated gene, Hfe, exhibit late-onset (18 months) RPE hypertrophy and hyperplasia, presumably as a result of iron accumulation (75). Similarly, iron buildup in the RPE of ceruloplasmin/hephaestin double-knockout mice leads to RPE hyperplasia and hypertrophy, with increased autofluorescent deposits in 7- to 9-month-old animals (76). In vivo ribozyme-mediated knockdown of murine manganese superoxide dismutase, which is encoded by the nuclear gene Sod2 and which localizes to the mitochondrial matrix, causes "distended" RPE with vacuoles and autofluorescent aggregates (77).…”
Section: Discussionmentioning
confidence: 99%
“…Mice homozygous for a null mutation in the hemochromatosisassociated gene, Hfe, exhibit late-onset (18 months) RPE hypertrophy and hyperplasia, presumably as a result of iron accumulation (75). Similarly, iron buildup in the RPE of ceruloplasmin/hephaestin double-knockout mice leads to RPE hyperplasia and hypertrophy, with increased autofluorescent deposits in 7- to 9-month-old animals (76). In vivo ribozyme-mediated knockdown of murine manganese superoxide dismutase, which is encoded by the nuclear gene Sod2 and which localizes to the mitochondrial matrix, causes "distended" RPE with vacuoles and autofluorescent aggregates (77).…”
Section: Discussionmentioning
confidence: 99%
“…Ceruloplasmin knockout mice exhibited morphologic and molecular features of agerelated macular degeneration. 23 Furthermore, ceruloplasmin was detected in seven of ten patients with exfoliation syndrome, but in only one of the eight controls. 13 In our study, we did not find a significant difference between patients and controls in terms of ceruloplasmin activity.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, mice deficient in the ferroxidases ceruloplasmin and hephaestin accumulate iron in the retina and subsequently have retinal degeneration with features of age-related macular degeneration. 2,3 In these mice, iron chelation with the orally absorbed and cellpermeant iron chelator deferiprone (Ferriprox) ameliorated oxidative stress and protected against iron overload-induced retinal degeneration. 4 Because other investigators showed that the iron chelator deferoxamine can protect against retinal light damage and retinal ischemia reperfusion injury, Hadziahmetovic et al 5 decided to test the recently US Food and Drug Administration-approved drug deferiprone because it is orally absorbed and has not been associated with retinal toxic effects in patients or mice.…”
Section: Xidative Stress Has Been Implicatedmentioning
confidence: 99%